Psychosocial, health and demographic characteristics of quality of life among patients with acute myeloid leukemia and malignant lymphoma who underwent autologous hematopoietic stem cell transplantation - Slovacek, Ladislav; Slovackova, Birgita; Jebavy, Ladislav; Macingova, Zuzana (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: This study evaluated the effect of selected psychosocial, health and demographic characteristics of quality of life (QOL) among patients treated with autologous hematopoietic stem cell transplantation (HSCT). DESIGN AND SETTING: This was a retrospective study at Charles University Hospital, Hradec Kralove. METHODS: The Czech version of the international generic European Quality-of-Life questionnaire (EQ-5D) was applied to evaluate QOL among patients with acute myeloid leukemia (AML) and malignant Hodgkin’s and non-Hodgkin’s lymphoma (ML). The total number of respondents was 36: 12 with AML (seven males and fi ve females) and 24 with ML (11 males and 13 females). The mean age of AML respondents was 46 years and the mean age of ML respondents was 44.5 years. RESULTS: Age, smoking status and education level had statistically signifi cant effects on QOL among AML respondents (p < 0.05), and age had a statistically signifi cant effect on QOL among ML respondents (p < 0.05). The overall QOL among AML and ML respondents was generally good: the mean EQ-5D score among AML respondents was 71.5% and among ML respondents it was 82.7%. CONCLUSION: The QOL among AML and ML respondents treated with autologous HSCT was good. However, patients more than 50 years old, smokers and patients with lower education levels presented worse QOL. These fi ndings need to be better evaluated in longitudinal studies, using large samples.